Evolution of anisotropic magnetic properties through helix-to-fan transition in helical antiferromagnetic EuCo2As2 - Jong Hyuk Kim; Mi Kyung Kim; Jae Min Hong; Hyun Jun Shin; Ki Won Jeong; Jin Seok Kim; Kyungsun Moon; Nara Lee; Young Jai Choi (Communications Physics, 2023)
Antiferromagnetic systems are prospective materials for spintronic applications due to increased stability and speed of the magnetisation dynamics. Here, the authors use torque magnetometry and an easy-plane anisotropic model to investigate and understand the magnetic anisotropy of the non-collinear antiferromagnet EuCo2As2.